The Relationship of Sanitation Hygiene with The Presence of Echericia Coli on Jamu Beras Kencur in The Official Village of Banjarbaru City - Imanuela S. S, Dea Rama; Noraida, Noraida; Erminawati, Erminawati; Isnawati, Isnawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Jamu is a traditional medicine originating in Indonesia. We process herbal medicine from natural plants without using chemical additives as additional ingredients. Herbal medicine must meet health standards by BPOM Regulation, namely Escherichia coli negative. Escherichia coli found on jamu beras kencur can cause health problems for those who consume it. The Banjarbaru City Official Village is a collection of herbal medicine makers and traders. This study aimed to determine the correlation between hygiene and sanitation in the manufacture of jamu beras kencur and the presence of Escherichia coli in jamu beras kencur in Kampung Pesantren Banjarbaru City. The research type was an analytical and cross-sectional design approach. There were 13 makers and samples of jamu beras kencur. We gathered the data through observation and utilized laboratory testing techniques for MPN. Data analysis used the Spearman rank correlation test. Observations of herbal medicine makers' hygiene and sanitation conditions revealed that 7 (53.8%) fell into the excellent category. The results of laboratory examinations obtained by as many as seven (53.8%) met the requirements. The results of the Spearman test showed a correlation between hygiene and sanitation with Escherichia coli on jamu beras kencur in Kampung Pesantren Banjarbaru City. Herbalists use gloves, head coverings, masks, and aprons during herbal medicine processing to improve the bacteriological quality of the medicine. They also ensure that their nails are short, maintained, and cleaned. Herbalists process herbal medicine using boiling water as the raw material and adhering to strict hygiene and sanitation protocols.